New Australian Hexactinellida (Porifera) with a revision of Euplectella aspergillum - Tabachnick, Konstantin R.; Janussen, Dorte; Menschenina, Larisa (Zootaxa, 2008)
In this study we found 28 species, 6 new to science, from 17 genera and 11 families. Four families: Aphrocallistidae, Rossellidae, Monorhaphididae and Euretidae have not been reported from the Australian seas before. Revision of the famous ’Venus-flower basket’ Euplectella aspergillum has accompanied this investigation, which led to designation of the following subspecies defined by specific features and various geographical distributions: E. aspergillum regalis (formerly E. regalis Schulze), E. aspergillum australicum, nov. ssp., E. aspergillum indonesicum, nov. ssp. and E. aspergillum aspergillum.